Some lessons from the Kenya Livestock Development Project - Solomon Bekure; Dyson-Hudson, N.; Grandin, B.E.; Semenye, P.P.; Pasha, I.K.O.; Chabari, F.N. (International Livestock Centre for Africa, 1982)
A summary report on impact evaluation of Kenya Livestock Development Project. Examines company and group ranches. Discusses infrastractual development, organization and management, cattle herd structure, and education. Relates individual and group ranches.